Рішення для зменшення енергоспоживання базовими станціями в безпроводових мережах - Котолупенко, Б. О. (ХНУРЕ, 2024)
It is proved that the existence of the problem of growing energy consumption caused by the need to increase capacity is important for telecommunication networks. It is analysed that the BS is considered to be the main element of the network that consumes the largest part of energy. Possible solutions aimed at energy saving of the BS are presented. It is shown that to solve the problems of energy saving, approaches should be used both at the architectural level and by increasing the efficiency of individual network components.
Keywords: зменшення енергоспоживання; базова станція